Optimization of pumpkin and feed moisture content to produce healthy pumpkin-germinated brown rice extruded snacks - na Sakon Nakhon, Phanlert Promsakha; Jangchud, Kamolwan; Jangchud, Anuvat; Charunuch, Chulaluck (Agriculture and Natural Resources, 2018)
The effects of three levels of pumpkin flour (PF; 10, 20 and 30%) and three levels of feed moisture content (FM; 13, 16 and 19%) on the physical properties, antioxidant activity and sensory properties of pumpkingerminated brown rice extrudates were investigated. The increase in the PF increased the bulk density, hardness, total phenolic content (TPC) and antioxidant activity, but decreased the expansion ratio of the extruded snack. Decreasing the FM caused an increase in the TPC and antioxidant activity of the snack product. The predicted optimum formulation of extrudates using response surface methodology was 10-13% PF and 13-14% FM under extrusion conditions at 140 °C (zone 6) and 350 rpm screw speed. These conditions produced extruded snacks with TPC values of 20-28 mg GAE/100 g sample on a dry basis and appearance and hardness liking scores of more than 6.5 (on a 9-point hedonic scale). Therefore, the results of this study supported the utilization of PF and germinated brown rice flour to develop healthy snack products.